Assessment and Treatment Recommendations for Pediatric Pain: The Influence of Patient Race, Patient Gender, and Provider Pain-Related Attitudes - Miller, Megan M. (J Pain, 2019)
Previous studies have documented that racial minorities and women receive poorer pain care than their demographic counterparts. Providers contribute to these disparities when their pain-related decision-making systematically varies across patient groups. Less is known about racial and gender disparities in children with pain or the extent to which providers contribute to these disparities. In a sample of 129 medical students (henceforth referred to as "providers"), Virtual Human methodology and a pain-related version of the Implicit Association Test (IAT) were used to examine the effects of patient race/gender on providers’ pain assessment/treatment decisions for pediatric chronic abdominal pain, as well as the moderating role of provider implicit pain-related race/gender attitudes. Findings indicated that providers rated Black patients as more distressed (mean difference [MD] = 2.33, P < .01, standard error [SE] = .71, 95% confidence interval [CI] = .92, 3.73) and as experiencing more pain-related interference (MD = 3.14, P < .01, SE = .76, 95% CI = 1.63, 4.64) compared to White patients. Providers were more likely to recommend opioids for Black patients than White patients (MD = 2.41, P < .01, SE = .58, 95% CI = 1.05, 3.76). Female patients were perceived to be more distressed by their pain (MD = 2.14, P < .01, SE = .79, 95% CI = .58, 3.70) than male patients, however there were no gender differences in treatment recommendations. IAT results indicated that providers held implicit attitudes that Black Americans (M = .19, standard deviation [SD] = .29) and males (M = .38, SD = .29) were more pain-tolerant than their demographic counterparts; however, these implicit attitudes did not significantly moderate their pain assessment/treatment decisions. Future studies are needed to elucidate specific paths through which the pain experience and care of children differ across racial and gender groups. PERSPECTIVE: Providers’ pain assessment (ie, pain distress/pain interference) and treatment (ie, opioids) of pediatric pain differs across patient race and to a lesser extent, patient gender. This study represents a critical step in research on pain-related disparities in pediatric pain.